Austrolebias arachan (Cyprinodontiformes, Rivulidae), a new species of annual fish from northeastern Uruguay - Loureiro, Marcelo (2004)
The annual fish Austrolebias arachan is described from temporary ponds of Río Tacuarí (Los PatosMerín system) and Río Negro (Río Uruguay drainage) basins. Austrolebias arachan is easily distinguished from other Austrolebias species by the combination of the following characters: body of males dark brown to black, with light narrow yellow vertical bands, dorsal fin dark brown with vertically elongated light yellow dots in the proximal half, pectoral fin light grey with margin black; females with anterior anal fin rays elongated, forming a triangular-shaped fin. Both sexes with pelvic fins joined to each other in different degrees; two to four parietal neuromasts; three pectoral radiais in most individuals. The new species is closely related to A. adloffi species group and to A. viarius.